2008
DOI: 10.3892/mmr.1.4.537
|View full text |Cite
|
Sign up to set email alerts
|

Fucoidan, a major component of brown seaweed, prohibits the growth of human cancer cell lines in vitro

Abstract: Abstract. Fucoidan, the general term for sulfated polysaccharides, is reported to engage in various biological activities having anti-tumor, anti-coagulation and anti-viral effects. Though it has been investigated, the mechanism of its antitumor effects remains elusive. The current study examined the anti-tumor effects of fucoidan extracted from Okinawa mozuku on 15 human cancer cell lines (6 hepatocellular carcinomas, 1 cholangiocarcinoma, 1 gallbladder cancer, 2 ovarian cancers, 1 hepatoblastoma, 1 neuroblas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 9 publications
(16 reference statements)
1
39
0
Order By: Relevance
“…Many kinds of algae are traditionally used as a variety of foods, especially in East Asia, and have received considerable attention over the years as wholesome foods. Recent studies have found that fucoidans show various biological activities, including anticoagulant, 1) antiviral, 2) antitumoral, 3) and immunomodulating activities.…”
mentioning
confidence: 99%
“…Many kinds of algae are traditionally used as a variety of foods, especially in East Asia, and have received considerable attention over the years as wholesome foods. Recent studies have found that fucoidans show various biological activities, including anticoagulant, 1) antiviral, 2) antitumoral, 3) and immunomodulating activities.…”
mentioning
confidence: 99%
“…Previous studies have shown that fucoidan has significant biological activities, such as anti-bacterial (2), anti-viral (3), anti-coagulant (4), anti-oxidant (5), anti-inflammatory (4,6) and immunomodulatory effects (2,7). Other studies also described anti-carcinogenic properties (8)(9)(10)(11)(12)(13)(14)(15). For example, in vitro studies demonstrated that fucoidan can inhibit cell proliferation and induce cell death in numerous cell lines, including human bile duct cancers (8), nonsmall-cell bronchopulmonary carcinoma (9) and lymphoma (10).…”
Section: Introductionmentioning
confidence: 91%
“…Previous in vitro and in vivo studies have demonstrated the anti-cancer properties of fucoidan, including the suppression of growth (8,9,12,13), metastasis (11,15), angiogenesis (11,14), and the induction of apoptosis (8,10,32) and autophagy (32) in a variety of cancer cells. In the present study, fucoidan was effective in inhibiting the growth of implanted S-180 cells, but this effect was not mirrored in the in vitro studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fucoidan at 1.0 mg/ml concentration increased the G0/G1-phase population in hepatocarcinoma cell line (Huh7) accompanying by a decrease in the S phase, suggesting that fucoidan may cause the cell cycle arrest at the G0/G1 phase [86]. Fucoidan suppressed cell proliferation and arrest cell cycle in HCC cell lines (HAK-1A, KYN-2, KYN-3) and increased number of cells in the G2/M phase at 72 h after the addition of the fucoidan (22.5 μg/ml) [87]. Also identified that fucoidan induced the accumulation of cells in G1/S phase of the cell cycle of HUT-102 cells (T-cell lymphoma) [28] and non-small-cell human bronchopulmonary carcinoma (NSCLC-N6) cells [25].…”
Section: Effects Of Fucoidan On Cell Cycle and Apoptosismentioning
confidence: 99%